OPTIMASI COATING PUPUK UREA PRILL DENGAN POLIURETAN SEBAGAI APLIKASI CRF (CONTROLLED RELEASE FERTILIZER) - Suciati, Dwimaryam; Septiana, Yuli Amitha (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2024)
Urea fertilizer in prill form is widely used for the food crop and industrial segments due to its high nitrogen content, easy solubility in water, and hygroscopic nature, making it suitable as a CRF (Controlled Release Fertilizer). CRF is a type of fertilizer that releases nutrients, specifically nitrogen, gradually and periodically, closely matching the absorption pattern of plants, ensuring that the nutrients are not washed away by water and are effectively utilized. In this study, CRF was made by coating urea with polyurethane using the pouring method. The optimum condition of the CRF was determined by testing the total nitrogen content using the Kjeldahl method and measuring the crushing strength. The optimum value was obtained with variable 2 (urea: coating agent at 98%: 2%) with a total nitrogen content of 45.5% and a crushing strength of 0.9 KgF.